A Palimpsest of Place. Renovation of the Old Starosty Complex and Medieval Cellars in Olkusz - Nawrot, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The structure and methods of separating the space in consciously formed objects are a reflection of philosophical theories and historical processes, a specific emanation of the ocentricism, anthropocentrism and anti-centrism. Constructing the structure of an architectural object, i.e., separating space for it and within it, is determined by types of activities, methods, and purpose.
Keywords: renovation; architectonics; supra-architectural system; building anatomy; renowacja; architektonika; przestrzeń architektoniczna; piwnice średniowieczne; renowacja zespołu starostwa